2013
DOI: 10.3109/2000656x.2013.870909
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of proximal interphalangeal joint fractures by the pins and rubbers traction system: a follow-up

Abstract: A fracture of the proximal interphalangeal (PIP) joint at the base of the middle phalanx is rare, but is a challenge to treat. Posttraumatic osteoarthritis is a known complication causing impaired hand function and disability. The aim of the present retrospective study was to evaluate characteristics and outcome of complex PIP joint fractures treated by the pins and rubbers traction system (PRTS). Medical records of 42 patients with fractures treated with a PRTS in 1999-2010 were reviewed, and followed-up by q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
3
7
0
Order By: Relevance
“…Of these 29 articles that underwent final review and identified fracture type, 26 reported data on dorsal fracture-dislocations, 5 reported data on pilon fracture-dislocations, and 1 on volar fracture-dislocations, with 1 article reporting two fracture types, 10 and 1 article reporting data on all three fracture types. 18…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 29 articles that underwent final review and identified fracture type, 26 reported data on dorsal fracture-dislocations, 5 reported data on pilon fracture-dislocations, and 1 on volar fracture-dislocations, with 1 article reporting two fracture types, 10 and 1 article reporting data on all three fracture types. 18…”
Section: Resultsmentioning
confidence: 99%
“…A total of 48 articles were included in the final review, 5-52 25 of which reported data on dynamic external fixation, 12 on open reduction, 6 on hemi-hamate arthroplasty, 4 on extension block pinning, and 3 on percutaneous fixation. Two studies reported data on more than one group.…”
Section: Resultsmentioning
confidence: 99%
“…Postoperative osteoarthritic changes after treatment with external dynamic fixators develop in 12.5-61% of the cases ranging from mild to moderate changes [7,8,23]. In most of the studies, small residual articular step offs are described, which may cause osteoarthritic changes.…”
Section: Discussionmentioning
confidence: 99%
“…When fractures enter the articular surface of the phalangeal base or condyle, operative fixation should be sought unless less than 1 mm of gap or step-off is present. Fractures can range from simple articular fractures, fixed with K-wires or screws, to comminuted pilon-type fractures which may require a distraction fixator in order to restore articular alignment through ligamentotaxis [ 82 84 ].…”
Section: Introductionmentioning
confidence: 99%